Novel Inhibitors of DNA Repair Enzyme TDP1 Combining Monoterpenoid and Adamantane Fragments - Mozhaitsev, Evgenii S; Zakharenko, Alexandra L; Suslov, Evgeniy V; Korchagina, Dina V; Zakharova, Olga D; Vasil'eva, Inna A; Chepanova, Arina A; Black, Ellena; Patel, Jinal; Chand, Raina; Reynisson, Jóhannes; Leung, Ivanhoe K H; et al. (Anti-cancer agents in medicinal chemistry, 2019)
The DNA repair enzyme tyrosyl-DNA-phosphodiesterase 1 (TDP1) is a current inhibition target to improve the efficacy of cancer chemotherapy. Previous studies showed that compounds combining adamantane and monoterpenoid fragments are active against TDP1 enzyme. This investigation is focused on the synthesis of monoterpenoid derived esters of 1-adamantane carboxylic acid as TDP1 inhibitors. New esters were synthesized by the interaction between 1-adamantane carboxylic acid chloride and monoterpenoid alcohols. The esters were tested against TDP1 and its binding to the enzyme was modeling. 13 Novel ester-based TDP1 inhibitors were synthesized with yields of 21-94%; of these, nine esters had not been previously described. A number of the esters were found to inhibit TDP1, with IC50 values ranging from 0.86-4.08 µM. Molecular modelling against the TDP1 crystal structure showed a good fit of the active esters in the catalytic pocket, explaining their potency. A non-toxic dose of ester, containing a 3,7- dimethyloctanol fragment, was found to enhance the cytotoxic effect of topotecan, a clinically used anti-cancer drug, against the human lung adenocarcinoma cell line A549. The esters synthesized were found to be active against TDP1 in the lower micromolar concentration range, with these findings being corroborated by molecular modeling. Simultaneous action of the ester synthesized from 3,7-dimethyloctanol-1 and topotecan revealed a synergistic effect.